Analysis of Pes Cavus Leg Shape with Physical Performance of Members Flag Hoisting Team. - laskar satria, asa; pramono, harry; irawan, Fajar Awang (Universitas Negeri Semarang, 2025)
Members of the Flag Hoisting Team are selected through a strict selection. The selection participants must have certain physical criteria, such as ideal height and weight, firm posture, and excellent health. To become a candidate for Flag Hoisting Teamka, you can do it by examining the anatomical shape of the pedic arch. This study aims to analyze the shape of the pes cavus foot with the physical performance of the candidate for Flag Hoisting Teamka in Central Lampung regency. This study uses a quantitative method with a correlational descriptive approach. The research population consisted of 60 members who were preparing for the Flag Hoisting Teamka selection test in Central Lampung Regency, but only 37 samples met the research criteria. Samples were taken from students of SMAN Negeri 1 Punggur and Madrasah Aliyah Ma'arif 9 Kotagajah. Data was collected through observation, interviews, and documentation. Quantitative data analysis was carried out using microsoft excel, normality test, and correlation test, with SPSS software assistance version 27. The results showed a strong correlation, with the normality test indicating that the variables of Leg Shape (.134), Endurance (.181), Focus (.053), Balance (.053), Coordination (.200), and Muscle Strength (.200) were in the normal category. In addition, the correlation test produced a significance value (Sig.) of 0.001, which indicates a statistically significant relationship. The results showed that the group of women needed special attention because their endurance was in the very low category, which was influenced by biological factors such as muscle strength, hemoglobin, and lung capacity.